Dendritic Cell-Derived Artificial Microvesicles Inhibit RLS40 Lymphosarcoma Growth in Mice via Stimulation of Th1/Th17 Immune Response - Oleg V. Markov; Aleksandra V. Sen'kova; Islam S. Mohamed; Elena V. Shmendel; Mikhail A. Maslov; Anastasiya L. Oshchepkova; Evgeniy V. Brenner; Nadezhda L. Mironova; Marina A. Zenkova (MDPI AG, 2022)
Cell-free antitumor vaccines represent a promising approach to immunotherapy of cancer. Here, we compare the antitumor potential of cell-free vaccines based on microvesicles derived from dendritic cells (DCs) with DC- and cationic-liposome-based vaccines using a murine model of drug-resistant lymphosarcoma RLS40 in vivo. The vaccines were the following: microvesicle vaccines-cytochalasin B-induced membrane vesicles (CIMVs) obtained from DCs loaded with total tumor RNA using cholesterol/spermine-containing cationic liposomes L or mannosylated liposomes ML; DC vaccines-murine DCs loaded with total tumor-derived RNA using the same liposomes; and liposomal vaccines-lipoplexes of total tumor-derived RNA with liposomes L or ML. Being non-hepatotoxic, CIMV- and DC-based vaccines administered subcutaneously exhibited comparable potential to stimulate highly efficient antitumor CTLs in vivo, whereas liposomal vaccines were 25% weaker CTL inducers. Nevertheless, the antitumor efficiencies of the different types of the vaccines were similar: sizes of tumor nodes and the number of liver metastases were significantly decreased, regardless of the vaccine type. Notably, the booster vaccination did not improve the overall antitumor efficacy of the vaccines under the study. CIMV- and DC- based vaccines more efficiently than liposome-based ones decreased mitotic activity of tumor cells and induced their apoptosis, stimulated accumulation of neutrophil inflammatory infiltration in tumor tissue, and had a more pronounced immunomodulatory activity toward the spleen and thymus. Administration of CIMV-, DC-, and liposome-based vaccines resulted in activation of Th1/Th17 cells as well as the induction of positive immune checkpoint 4-1BBL and downregulation of suppressive immune checkpoints in a raw PD-1 >>> TIGIT > CTLA4 > TIM3. We demonstrated that cell-free CIMV-based vaccines exhibited superior antitumor and antimetastatic activity in a tumor model in vivo. The obtained results can be considered as the basis for developing novel strategies for oncoimmunotherapy.